2019
DOI: 10.1177/0748730419878036
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ligases Spsb1 and Spsb4 Regulate RevErbα Degradation and Circadian Period

Abstract: The time-dependent degradation of core circadian clock proteins is essential for the proper functioning of circadian timekeeping mechanisms that drive daily rhythms in gene expression and, ultimately, an organism’s physiology. The ubiquitin proteasome system plays a critical role in regulating the stability of most proteins, including the core clock components. Our laboratory developed a cell-based functional screen to identify ubiquitin ligases that degrade any protein of interest and have started screening f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 49 publications
1
13
1
Order By: Relevance
“…These results are somewhat different to our previous results in U2OS cells (which are female [21]) where SIAH2 knockdown blunted expression of REVERBα targets coincident with altered REVERBα protein turnover [10]. However, in the liver, we were surprised to find that SIAH2 loss had little effect on rhythms of REVERBα protein abundance rhythms of either sex (S1 Fig), possibly owing to tissue-specific compensation by other ubiquitin ligases [22][23][24]. Thus, it is not clear if these effects of SIAH2 loss are through alterations in REVERBα function, though female-specific regulation of REVERBα is not expected given its role in circadian regulation.…”
Section: Plos Geneticscontrasting
confidence: 99%
“…These results are somewhat different to our previous results in U2OS cells (which are female [21]) where SIAH2 knockdown blunted expression of REVERBα targets coincident with altered REVERBα protein turnover [10]. However, in the liver, we were surprised to find that SIAH2 loss had little effect on rhythms of REVERBα protein abundance rhythms of either sex (S1 Fig), possibly owing to tissue-specific compensation by other ubiquitin ligases [22][23][24]. Thus, it is not clear if these effects of SIAH2 loss are through alterations in REVERBα function, though female-specific regulation of REVERBα is not expected given its role in circadian regulation.…”
Section: Plos Geneticscontrasting
confidence: 99%
“…However, in the liver, we were surprised to find that SIAH2 loss had little effect on rhythms of REVERBα protein abundance rhythms of either sex (Suppl. Fig S1 ), possibly owing to tissue-specific compensation by other ubiquitin ligases (21)(22)(23). Thus, it is not clear if these effects of SIAH2 loss are through alterations in REVERBα function, though female-specific regulation of REVERBα is not expected given its role in circadian regulation.…”
Section: Resultsmentioning
confidence: 99%
“…These two apparently contradictory functions likely depend on how subsegments within these first 25AAs interact with each other. The mapping of the SPSB4 binding site to AA4-9 of REV-ERB is exciting (Figures 5 and 6), since our previous experiments showed that SPSB4knockdown will result in the stabilization of REV-ERB, as well as a longer circadian period (13). The shortfall of these ubiquitin ligase knockdown experiments is that one can always argue that the observed effects may be due to other possible targets of the ubiquitin ligase.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have investigated how various ubiquitin ligases contribute to the degradation of REV-ERB and their effects on the circadian clock (12)(13)(14)(15)(16). In this study, we focused on trying to understand the central events that need to happen to REV-ERB protein itself for degradation to take place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation